Getting to the bottom of ageing - Abd Razak, Dzulkifli (2003)
ON the last day of October 2003, the world’s oldest known woman died at the age of 116. Barely a month before, the oldest documented man died at the age of 114. Both were Japanese, symbols of the nation’s grey population with many centenarians among them. In fact, in Japan, “Respect for the Aged Day" is a national holiday to recognise those who have reached their 65th birthday, and this involves almost one in five. According to UN’s Population Division, in 2000 Japan ranked fourth in the list of world's "oldest” countries with 17 per cent of its population 65 years and above.